Engineering of T7 DNA-dependent RNA polymerase with activity at elevated temperature - Svenja Hehn; Julia Gutbrod; Maxi Gutjahr; Andreas Marx (PLoS ONE, 2026)
Bacteriophage T7 RNA polymerase (T7 RNAP) is a key enzyme for in vitro transcription (IVT) and plays a central role in the production of synthetic mRNA for research and therapeutic applications. However, IVT frequently generates double-stranded RNA (dsRNA) as an undesired by-product, which can trigger innate immune responses and compromise mRNA quality. Increasing reaction temperatures reduces dsRNA formation, however, the wild-type T7 RNA polymerase exhibits limited stability under such conditions. Therefore, polymerase variants with enhanced thermotolerance enable more robust transcription at elevated temperatures while minimizing dsRNA generation. To address this limitation, we aimed at obtaining T7 RNA polymerase variants with increased thermotolerance using the Protein Repair One Stop Shop (PROSS) web server. Four crystal structures of T7 RNA polymerase, comprising a promoter complex, an initiation complex, and two elongation complexes were used as input for independent PROSS runs. Mutations shared across all four designs for each PROSS index were then combined to generate multi-structure PROSS Combined Designs (PCDs). In the subset evaluated experimentally, PCD9 retained full-length transcription activity at temperatures up to 48 °C, whereas wild-type T7 RNA polymerase showed strong loss of activity under the same buffer conditions. At 48 °C, PCD9 supported the synthesis of kilobase-length scale transcripts and produced no detectable dsRNA signal in a dot blot assay. In contrast, the wild-type enzyme generated strong dsRNA signals at 37 °C and failed to produce detectable RNA at 48 °C. Additional PROSS variants derived exclusively from the elongation complex structure were inactive at both 37 °C and 48 °C. Together, these results show that multi-structure PROSS design can yield a thermotolerant T7 RNA polymerase with improved performance at elevated temperature and reduced dsRNA byproduct formation. The findings also suggest that restricting stability design to a single structural state may not fully capture the requirements of a highly dynamic enzyme.